Caracterização estrutural do sistema de falhas Santa Barbara - Região de Caçapava do Sul - Lavras do Sul - Trevisol, Andreá (Universidade do Vale do Rio dos Sinos, 2007)
This Works present the structural characterization of the Santa Bárbara system of faults, based in analysis of radar images, electroresistivity profiles (lateral profiling technique) and field data's. The Santa Bárbara system of faults is a mega structure from the Sul-riograndense shield. With NE-SW orientation, it extend from the region where emerge the Caçapava do Sul Granite Complex, at NE, since the region where emerge the Lavras do Sul Granite Complex, at SW, passing by Santa Bárbara Sub-basin from Camaquã Basin. Are constituents of this system, faults knows like, Perau's Fault, Cabritos' Fault and Segredo's Fault. The analysis of radar images detaches lineaments with big extensions (a set of ten km) closely rectilineal, uplifted blocks (normal flower structures), lowered blocks (negative flower structures, pull-apart basins) and imbricate fans, besides Riedel's structures (secondary faults and fractures). The electroresistivity profiles show that the mains lineaments represent planes of vertical discontinuity. The analysis of outcrops shows that in the areas with the influence of the main lineaments and Riedel structures occurs a brittle deformation zones, representatives of the deformation in a high crustal level. The information permits to characterize the Santa Bárbara system of fault as a left-handed strike slip system, where along of, are alternated structures formed in transtensive or transpressive domains. The deformation is associated a system of stress axis, with σ1 oriented at N-S direction, σ2 closely vertical, and σ3 with orientation E-W. The fault system has influenced in the emplacement of Caçapava do Sul Granite Complex and in the sedimentation of the Santa Bárbara sub-basin from Camaquã basin, and has your main functionament period to near of 540 Ma.
Keywords: Sistema de Falhas Santa Bárbara; Geologia estrutural; Complexo Granítico Caçapava do Sul; ACCNPQ::Ciências Exatas e da Terra::Geologia